Resting State Vagally-Mediated Heart Rate Variability Is Associated With Neural Activity During Explicit Emotion Regulation - Steinfurth, Elisa C. K.; Wendt, Julia; Geisler, Fay; Hamm, Alfons O.; Thayer, Julian F.; Koenig, Julian (Frontiers in Neuroscience, 2018)
Resting state vagally-mediated heart rate variability (vmHRV) is related to difficulties in emotion regulation (ER). The prefrontal cortex (PFC) provides inhibitory control over the amygdala during ER. Previous studies linked vmHRV with activity in the ventromedial PFC (vmPFC) during implicit ER. To date no study examined the relation between vmHRV and brain activity during explicit ER. vmHRV was measured during a 7 minutes baseline at T1 2-5 days preceding T2. At T2 n = 24 participants (50% female, Mage=24.6 years) viewed neutral or emotional pictures of pleasant or unpleasant valence and were instructed to intensify or to reduce their present emotion using two ER strategies (reappraisal and response modulation) or to passively view the picture. Participants rated the valence of their emotional state from pleasant to unpleasant after ER. Whole-brain fMRI data were collected using a 1.5-T-scanner. We observed an association between resting state vmHRV and brain activation in the PFC and the amygdala during ER of unpleasant emotions. Groups based on vmHRV showed significant differences in the modulation of amygdala activity as a function of ER strategy. In participants with high vmHRV amygdala activity was modulated only when using reappraisal and for low vmHRV participants only when using response modulation. Similar, dorsomedial PFC activity in high vmHRV participants was increased when using reappraisal and in low vmHRV participants when using response modulation to regulate unpleasant emotions. These results suggest that individuals with low vmHRV might have difficulties in recruiting prefrontal brain areas necessary for the modulation of amygdala activity during explicit ER.